Hepatitis C virus associated glomerulopathies - Ozkok, Abdullah (Baishideng Publishing Group Inc, 2014)
Hepatitis C virus (HCV) infection is a systemic disorder which is often associated with a number of extrahepatic manifestations including glomerulopathies. Patients with HCV infection were found to have a higher risk of end-stage renal disease. HCV positivity has also been linked to lower graft and patient survivals after kidney transplantation. Various histological types of renal diseases are reported in association with HCV infection including membranoproliferative glomerulonephritis (MPGN), membranous nephropathy, focal segmental glomerulosclerosis, fibrillary glomerulonephritis, immunotactoid glomerulopathy, IgA nephropathy, renal thrombotic microangiopathy, vasculitic renal involvement and interstitial nephritis. The most common type of HCV associated glomerulopathy is type I MPGN associated with type II mixed cryoglobulinemia. Clinically, typical renal manifestations in HCV-infected patients include proteinuria, microscopic hematuria, hypertension, acute nephritis and nephrotic syndrome. Three approaches may be suggested for the treatment of HCV-associated glomerulopathies and cryoglobulinemic renal disease: (1) antiviral therapy to prevent the further direct damage of HCV on kidneys and synthesis of immune-complexes; (2) B-cell depletion therapy to prevent formation of immune-complexes and cryoglobulins; and (3) nonspecific immunosuppressive therapy targeting inflammatory cells to prevent the synthesis of immune-complexes and to treat cryoglobulin associated vasculitis. In patients with moderate proteinuria and stable renal functions, anti-HCV therapy is advised to be started as pegylated interferon-α plus ribavirin. However in patients with nephrotic-range proteinuria and/or progressive kidney injury and other serious extra-renal manifestations, immunosuppressive therapy with cyclophosphamide, rituximab, steroid pulses and plasmapheresis should be administrated.